IMF Staff papers : Volume 33 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1986)
This paper examines how the effects of fiscal policies are transmitted internationally. The analysis emphasizes that fiscal shifts of recent years constitute major disturbances to saving and investment flows. An increase in a country's fiscal deficit corresponds to a higher level of public sector dissaving. For increased foreign saving to enter through the capital account, the current account deficit must rise via an appreciating real exchange rate. An autonomous rise in investment, such as that induced by US tax measures passed in 1981-1982, produces qualitatively similar effects in the short run. Simulations suggest that a permanent fiscal deficit reduction of 1 percent of capacity output in any one of the three largest industrial countries produces a significant decline in real interest rates and a large initial depreciation in that country's currency. US tax incentives for investment would induce higher interest rates and an appreciated dollar. Simulations of the combined effects of increased US investment and observed movements in inflation-adjusted deficits in all three countries in 1981-1985 suggest that substantial fractions of these interest and exchange rate movements were related to shifts in fiscal policy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange